PENGARUH KEPEMIMPINAN KEPALA MADRASAH TERHADAP PEMBINAAN LINGKUNGAN BELAJAR UNTUK MEWUJUDKAN EFEKTIVITAS PEMBELAJARAN (Penelitian di MTs Al-Fatwa, At-Ta’awun dan Al-Qomariyah Sukaresmi Garut) - Jajang Jajang; Endang Soetari Ad; Nenden Munawaroh (Jurnal Manajemen Pendidikan, 2026)
Objective: This study is motivated by the importance of maximising the effectiveness Of teaching and fostering a positive learning environment. The study aims to analyse the direct influence of the madrasah principal’s leadership on the fostering of the learning environment, the influence of the fostering of the learning environment on the effectivenessof teaching, and to examine the role of the fostering of the learning environment as amediating variable. The research was conducted at Madrasah Tsanawiyah Al-Fatwa, At-Ta’awun and Al-Qomariyah in Sukaresmi, Garut, as the research locations Methods: Method: A quantitative survey method was used on 65 teachers and analysed using Path Analysis. Results: Results: The leadership of the madrasah head had no significant effect on the development of the learning environment (Sig. = 0.968 > 0.05) and had no direct effect on the effectiveness of learning (Sig. = 0.958 > 0.05). Meanwhile, the fostering of the learning environment has a positive and highly significant effect on the effectiveness of learning (Sig. = 0.000 < 0.05). Novelty: Novelty:  (1) A direct relationship by testing the influence of the madrasah headteacher’s leadership on the development of the learning environment, rather than as a supporting variable; (2) measuring the effectiveness of learning from the perspective of the madrasah headteacher, not just teachers and students; (3) using a multi-site study to examine the leadership of the madrasah headteacher.